Pengaruh keberadaan habitat alami terhadap keanekaragaman dan kelimpahan serangga pengunjung bunga mentimun - Susilawati Susilawati; Damayanti Buchori; Akhmad Rizali; Pudjianto Pudjianto (Jurnal Entomologi Indonesia, 2017)
Presence of insects in agricultural habitat is affected by several factors such as natural habitat. The objective of this research was to study the effect of natural habitat on diversity and abundance of flower-visiting insects in cucumber fields. Ecological observation was conducted in 12 cucumbers fields located in regencies of Bogor, Cianjur, and Sukabumi, West Java. Cucumber fields were categorized in two different distant form natural habitat i.e. near natural habitat (less than 200 m) and far from natural habitats (more than 1000 m). The observations of flower-visiting insects in cucumber fields were conducted by counting the number of flower-visiting insects that perched within 100 flowers in four different transects. The result showed that the presence of natural habitat affected species richness but not the abundance of flower-visiting insects in cucumber field. The dominant species of flower-visiting insects in cucumber fields were Aphis sp., Tapinoma sp. and Thrips parvispinus Karny, while the most dominant pollinator was Apis cerana Fabricius. The distance of natural habitat from farmland affected the presence of flower-visiting insects especially pollinator insects that provide important services on enhancing crop yield.